2011
DOI: 10.1007/s00415-011-5915-2
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor imaging and olfactory identification testing in early-stage Parkinson's disease

Abstract: Evidence from imaging, clinical studies, and pathology suggests that Parkinson's disease is preceded by a prodromal stage that predates clinical diagnosis by several years but there is no established method for detecting this stage. Olfactory impairment, which is common in Parkinson's disease and often predates clinical diagnosis, may be a useful biomarker for early Parkinson's. Evidence is emerging that diffusion imaging parameters might be altered in olfactory tract and substantia nigra in the early stages o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
83
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(96 citation statements)
references
References 23 publications
10
83
1
Order By: Relevance
“…There is evidence suggesting that neurodegenerative changes occur outside the SN. When combined with olfactory testing, one study 22 found reduced FA of the anterior olfactory structures in patients with PD vs controls, and another study 18 found that patients with PD and anosmia have reduced FA in white matter near the gyrus rectus compared with controls (or patients with PD) with no olfactory dysfunction. Five studies found reductions in the frontal white matter, 4 significant.…”
Section: Resultsmentioning
confidence: 99%
“…There is evidence suggesting that neurodegenerative changes occur outside the SN. When combined with olfactory testing, one study 22 found reduced FA of the anterior olfactory structures in patients with PD vs controls, and another study 18 found that patients with PD and anosmia have reduced FA in white matter near the gyrus rectus compared with controls (or patients with PD) with no olfactory dysfunction. Five studies found reductions in the frontal white matter, 4 significant.…”
Section: Resultsmentioning
confidence: 99%
“…One recent DTI study has demonstrated a decrease in FA also in the anterior olfactory system at an early stage of PD (Rolheiser et al 2011). Of note, two meta-analyses on DTI in PD patients have been published, one claiming that DTI is promising biomarker in Parkinsonian syndromes (Cochrane and Ebmeier 2013) while the other was actually questioning stability and validity of nigral FA changes (Schwarz et al 2013).…”
Section: Introductionmentioning
confidence: 98%
“…TBSS-based analysis of FA values in central olfactory areas in Parkinson patients confirmed abnormal structural integrity [36]. A recent study found decreased FA values in the anterior central olfactory structures in Parkinson's disease [37]. The same study found Parkinson patients to have a significantly decreased identification function measured with the UPSIT (University of Pennsylvania Smell Identification) test.…”
Section: Discussionmentioning
confidence: 84%